PROGRESS AND RECENT RESEARCH OF TRANSPORTATION MODES IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW - Dessy Laresti, Rahayu; Arif , Ashari; Adika Bisma Dwi, Febriano; Muhammad A.I. , Wardoyo; Muhammad M.F. , Pratama; Dwi Prasetya , Adhi (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2024)
One of the main topics in the discussion of transportation geography is the mode of transportation. With its essential position, transportation modes have long received attention in various transportation geography studies. This paper presents information on the progress and trends of research topics on transportation modes with a geographical approach. This paper is a systematic literature review organized using the PRISMA approach. Search keywords were determined using the PICO method. The reviewed manuscripts were obtained from the Scopus database using the criteria of journal articles and research results, and they were in English. Two hundred seventy-four documents were collected since 1983, with peak productivity in 2020. One hundred ninety-nine articles were selected through the extraction process and continued with the review. In summary, this study offers new insights into the development trend of transportation mode studies in Indonesia.